2020
DOI: 10.1177/0145721720916179
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers of Sleep in Young Adults With Type 1 Diabetes

Abstract: Purpose The purpose of this study was to explore the perceived facilitators and barriers for obtaining sufficient sleep in young adults with type 1 diabetes (T1D). Methods A qualitative descriptive approach was used to generate data. In-depth semi-structured interviews with 30 young adults with T1D (66.7% female, mean age = 22.1 years) were conducted. Interviews were transcribed verbatim and coded using NVivo. Results Young adults with T1D reported feeling challenged at bedtime and overnight by the demands of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 42 publications
2
33
4
Order By: Relevance
“…Two overarching health goals emerged from the data, which included promoting sleep health and improving diabetes self-management. Barriers and facilitators of sleep health have been explored in young adults in the general population and two studies of individuals with T1D (Barnard et al, 2016; Griggs et al, 2020; Paterson et al, 2019). However, to the best of our knowledge, this is the first study where the sleep health goals of young adults with T1D have been captured and linked to their diabetes self-management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two overarching health goals emerged from the data, which included promoting sleep health and improving diabetes self-management. Barriers and facilitators of sleep health have been explored in young adults in the general population and two studies of individuals with T1D (Barnard et al, 2016; Griggs et al, 2020; Paterson et al, 2019). However, to the best of our knowledge, this is the first study where the sleep health goals of young adults with T1D have been captured and linked to their diabetes self-management.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to conduct a detailed exploration of sleep health goals of young adults with T1D who were followed over 6-14 days with a concurrent assessment of sleep characteristics and glycemia using wearable technologies (actigraphy and CGM) to provide context and insight into potential avenues to influence sleep and diabetes self-management behaviors. We have previously reported that higher sleep variability, daytime sleepiness, and sleep fragmentation were associated with higher glucose variability (Griggs et al, 2021) and general and diabetes-specific barriers and facilitators in young adults with T1D (Griggs et al, 2020). In this article, we describe findings from our qualitative descriptive study of young adults with T1D.…”
Section: Purposementioning
confidence: 90%
See 1 more Smart Citation
“…Previous quantitative and qualitative research also found technology to have a mixed impact on sleep, including promoting greater sleep quality and quantity as well as disrupting sleep. 6,8,15,34 In previous studies, partners of adults and parents of children with T1D reported disrupted sleep due to continuous glucose monitoring (CGM) alarms overnight. 15,34 On the other hand, CGM use in children is associated with fewer sleep disruptions, and individuals with T1D and their family members have described expectations about diabetes devices alleviating diabetes-specific worries and management burdens.…”
Section: Subtheme: Technologymentioning
confidence: 99%
“…these groups have identified themes related to general and diabetes-specific barriers to sleep, including electronic use before bed, homework and stress (general) and fear of hypoglycaemia, hyper-or hypoglycaemia and sensor/pump alarms (diabetes-specific). 7,8 Adults with T1D also selfreported poorer sleep quality, greater sleep disturbances, and more daytime dysfunction than individuals without T1D. 9 Sleep difficulties in youth with T1D negatively impact their parents' sleep and emotional functioning, and families of young people with T1D demonstrate a high prevalence of insufficient sleep duration.…”
mentioning
confidence: 99%